Langerhans cell histiocytosis in adults: literature review - V. G. Potapenko; V. V. Baykov; A. V. Zinchenko; N. A. Potikhonova (Онкогематология)
Langerhans cells histiocytosis is a variant of malignant histiocytosis. The course and symptoms vary. patients with localized forms have a better prognosis, because local therapy is effective. patients with multifocal forms of histiocytosis receive systemic drug therapy, which cures some of the patients. This review provides up-to-date data about typical presentation of the organ involvement, diagnosis, course and therapy of various forms of Langerhans cells histiocytosis.